Paleoenvironmental evolution of the Ediacaran Corumbá Group, Southern Paraguay Belt, based on traditional (C, O, Sr) and non-traditional (Cr, Cd) isotope chemostratigraphy - Fernandes, Henrique Albuquerque (2025)
Pronounced biologic and environmental changes unfolded during the Ediacaran Period (635538 Ma), ultimately marking the transition from an ancient Precambrian Earth to a more modern-like Phanerozoic Earth. A comprehensive understanding of this interval is essential to investigate the relationship between environment and early animal evolution. The Corumbá Group, in Midwest Brazil, is one of the main Ediacaran units for investigating Ediacaran paleoenvironments due to its wide exposure, relatively good preservation, and rich fossil content. The aim of this thesis is to present a geochemistry-based paleoenvironmental evolution of the Corumbá Group, discussing how these findings are related to the rise of primitive lifeforms. For this purpose, four studies were conducted, bringing new sedimentological and geochemical data, including traditional (C, O, and Sr) and non-traditional (Cr and Cd) stable isotopes, as well as rare earth elements (REE), obtained from outcrop and GRIND drill core samples (Geological Research through Integrated Neoproterozoic Drilling). In this study, a new geologic unit in the Corumbá Group was defined, termed Morraria do Sul Formation, which represents a post-Marinoan cap carbonate succession formed during a major transgression over glacial rocks of the Puga and Cerradinho formations and the basement. Negative Ce anomalies in tubestone-microbialites of this cap carbonate and radiogenic 87Sr/86Sr values reveal mildly oxygenated shallow waters affected by 87Sr-rich meltwater plumes. Furthermore, a pronounced increase in 114Cd and decrease in 53Cr upwards indicate a significant resumption of primary productivity immediately after the Marinoan Glaciation. The subsequent studies focus on the Tamengo and Bocaina formations, encompassing the ca. 565540 Ma interval. The Tamengo Formation in the Serra da Bodoquena region represents a storm-dominated mid- to outer-ramp setting, with redox-stratified water column, as revealed by the middle-REE-bulge pattern and sedimentary facies. Analysis of GRIND drill cores showed two complete transgression-regression cycles in the Bocaina and Tamengo formations, separated by a major sequence boundary in the form of an erosive surface. 13C values in the Bocaina Formation are positive, around +2, followed by a pronounced drop in the Bocaina-Tamengo limit, where they reach -2. The Tamengo Formation presents an increase in 13C up to +6. This 13C curve, as well as the abundance of Germinosphaera and Leiosphaeridia acritarchs, varies according to relative sea-level oscillations, revealing an eustatic control on carbon isotope excursions and microfossil abundance. The Sr, Cr, and Cd isotope records of the upper Corumbá Group show that the Bocaina Formation is consistent with an oligotrophic, semi-restricted, and predominantly anoxic setting, with a shallow chemocline. The Tamengo Formation, in turn, represents a more oxygenated setting connected with the open ocean and mainly oligotrophic, but punctuated by periods of eutrophication. These episodes raised the depth of the chemocline, causing expanded anoxia, and may have been caused by increased Fe input into the basin. These differences in the overall paleoceanographic scenario between the Bocaina and Tamengo formations may partially explain the occurrence of metazoan fossils only in the latter, which ultimately reveals an intricate coevolution of life and environment in the late Ediacaran.